Exploration Of Codon Usage Patterns In Some Brucella Genomes - ARVIND K GOYAL; ARNAB SEN; SAUBASHYA SUR; ASIM K BOTHRA (International Journal of Pharma and Bio Sciences, 2010)
Comparative analysis of codon usage patterns in some Brucella strains were performed to predict expression levels for protein coding genes, find out horizontally transferred pathogenesis related genes, investigate patterns of pathogenesis related genes with respect to expression levels and monitor involvement of predicted highly expressed genes with lifestyle of Brucella strains. Selection for translational efficiency plays a major role in codon usage variation. Codon bias is also strongly influenced by GC3 compositional constraints. Thirty-five PHX (potentially highly expressed) genes related to pathogenicity have also been identified in the seven strains. High number of PHX genes associated with the metabolism COG group divulges that metabolic genes has an important part to play in effecting the survival of the bacteria against the action of host’s resistance, antibiotics etc. thus establishing infection. Pathogenicity related homologs reveal that they help them to protect from the selective pressure of evolution.